I Can Read : Snowshoe Thompson - Levinson, Nancy Smiler; Sandin, Joan ([New York, N.Y.] : HarperCollins, 1992)
One winter John Thompson skis across the Sierra Nevada Mountains and creates a path upon which mail and people may travel, thus earning his nickname "Snowshoe Thompson."
Keywords: Thompson, Snowshoe, -- 1827-1876 -- Juvenile literature; Pioneers -- Biography -- Sierra Nevada (Calif. and Nev.); Sierra Nevada (Calif. and Nev.) -- Biography -- Letter carriers; Frontier and pioneer life -- Juvenile literature. -- Sierra Nevada (Calif. and Nev.); Sierra Nevada (Calif. and Nev.) -- History; Early chapter